Rheological study of food materials for 3D printing - Ng, Noel Zhi Kang (2019)
This final year project aims to develop two food inks that are suitable for 3D printing for patients with dysphagia. The two food choices taken into consideration were Thailand Yam and Sweet Corn Kernels. The food inks were formed with the addition of hydrocolloids. This report analyses how the addition of various hydrocolloids affects the rheological properties and 3D printability of the inks.